Effect of gradual pollen presentation on pollination efficiency and reproduction of Vaccinium corymbosum Berkeley in two habitats - Sun, Ke Xin; Zhang, Yan Jia; Zhou, Chun Zhi; Yang, Shan Lin; Jiang, Hui Xin; Cui, Rong Rong (Frontiers in Ecology and Evolution, 2024)
IntroductionGradual pollen presentation is a reproductive strategy for plants to improve the efficiency and accuracy of pollen export and acceptance as well as to promote outcrossing. Vaccinium corymbosum Berkeley has a typical mechanism of gradual pollen presentation.MethodsIn this study, we used indoor and outdoor observations to investigate the floral characteristics, pollination characteristics and breeding system of this species in open ground and greenhouse.ResultsThe results showed that the single white, inverted bell-shaped flower of V. corymbosum was able to effectively avoid the negative effects of rainfall, nectar dilution and pollen removal by wind, and improved pollen viability and the duration of stigma receptivity. The setting rate of ‘Northland’ is higher than open ground by artificial pollination in greenhouse, therefore, greenhouses are more suitable for ‘Northland’ reproduction. The gradual pollen presentation prolongs dispersal time, promotes pollinator participation in the pollination process, increases staminate fitness, and provides for nectar feeding by pollinators as well as pollen export. Bombus spp. and A. m. ligustica were effective pollinators in the open ground and greenhouse, and the pollination efficiency of Bombus spp. was higher than that of A. m. ligustica, and greenhouse pollination is more efficient than open ground. The coincidence of the peak period of pollinator visits with the period of highest pollen viability and optimal pollination of stigmas, as well as the high nectar production, could maximize the frequency of pollinator visits and increase the chances of successful pollination as well as the pollination efficiency.DiscussionTherefore, it is important to study the floral characteristics of V. corymbosum Berkeley and the mechanism of gradual pollen presentation in order to improve the pollination efficiency and promote the success of outcrossing, which can provide a theoretical basis for the breeding of V. corymbosum.